Fumonisina e seu efeitos sobre a expressão do genes IGF-I, GHR, SPL, CASP-7 e características de desempenho em tilápia-do-Nilo - Silva, Stefânia Caroline Claudino da (2015)
Fumonisin is a mycotoxin produced during the secondary metabolism of Fusarium verticillioides and Fusarium proliferatum and may cause several injuries and loss in performance in animals that consume them. In this study, the hypothesis that dietary intake of fumonisin affects the growth performance and the apoptotic balance was tested. Two experiments were performed. In the first, fingerlings of Nile tilapia (2.64 ± 0.06g) were fed diets containing different levels of fumonisin (0 mg/kg - control diet, 20 mg/kg, 40 mg/kg and 60 mg/kg) and were evaluated at an average feed intake (FI), weight gain (WG), feed efficiency (FE) and the gene expression of growth hormone receptor (GHR), insulin like growth factor 1(IGF-1), caspase7 (CASP 7) and sphingosine phosphate lyase (SPL) in hepatic tissue. All variables were evaluated at 15 and 30 days of treatment. Diets containing 20, 40 and FB 60 mg/kg diet significantly reduced the GP (p <0.0001), FE (p <0.0001), and the mRNA expression of GHR and IGF-1 both at 15 and 30 days of treatment. A reduction of the relative levels of SPL mRNA was observed for tilapias treated with FB 60mg/kg feed for 15 days (P <0.0001) and a significant increase of SPL mRNA was observed after 30 days (P <0.0001). Gene expression for CASP 7 was significantly reduced at 15 (P <0.0001) and 30 days (P = 0.0011).In the second experiment, fingerlings (2.63 ± 0.39g) and juveniles (75.9 ± 11g) of Nile tilapia were fed diets, with and without the inclusion of fumonisin (FB 50 mg/kg diet)for 20 daysin order to evaluate its effects on GPM, CRM, feed conversion (FC) and GHR mRNA expression and IGF-1 in the liver. The diet containing FB reduced the WG (p <0.0001) and worsened FC (p <0.0001) to fingerlings, but it does not affect the FI. For juveniles, the inclusion of fumonisin did not affect the FI, FC and BW. The mRNA expression of GHR and IGF-1 for fingerlings and for juveniles were significantly reduced by the inclusion of fumonisin (p <0.0001). These results indicate that the fumonisin affects the hepatic expression GHR, IGF-1, SPL and CASP 7, and that its effects on the performance of the Nile tilapia are dependent on dosage and time.